Biosafety assessment of Bifidobacterium animalis subsp. lactis AD011 used for human consumption as a probiotic microorganism. (November 2020) - Ku, Seockmo; Yang, Suyoung; Lee, Hyun Ha; Choe, Deokyeong; Johnston, Tony V.; Ji, Geun Eog; Park, Myeong Soo
Abstract: In this work, the previously identified Bifidobacterium strain, Bifidobacterium animalis subsp. lactis AD011 (obtained from an infant fecal sample), intended as a potential probiotic microorganism, is assessed for its safety using multiple in vitro virulence assays (ammonia and biogenic amine synthesis, hemolytic and mucin degradation activities, antimicrobial susceptibility and conjugal transferability of antibiotic resistance genes to other microorganisms) and comparative genomic analysis. The genome data of B. lactis AD011 was compared with genome sequences of two commercially available probiotic microorganisms ( Bifidobacterium lactis BB-12 and Bifidobacterium lactis Bl-04) which are designated as generally recognized as safe by the U.S. Food and Drug Administration. The results of these experiments showed no significant potential vulnerabilities and no side effects. B. lactis AD011 showed higher resistance to tetracycline than the European Food Safety Authority cut-off. However, the measured susceptibility is similar to or lower than that of other previously certified GRAS Bifidobacterium strains. Tetracycline resistance of B. lactis AD011 was not conveyed via conjugation with L. fermentum AGBG1, which is susceptible to tetracycline. Complete DNA sequencing of B. lactis AD011 showed the absence of transferable drug resistance plasmids. The three B. lactis strains (AD011, BB12 and Bl-14) compared in this study were found to share very close genomic sequence homology (>99.8%). Therefore, based on this study, B. lactis AD011 appears to be a safe, bioactive, bifidobacterial food ingredient, starter culture, and/or probiotic microorganism for human health.